Synthesis and characterization of new heterometallic cyanido complexes based on [Co(CN)6]3- building blocks: crystal structure of [Cu2(N-bishydeten)2Co(CN)6]•3H2O having a strong antiferromagnetic exchange - Korkmaz, Sengul Aslan; Karadag, Ahmet; Yerli, Yusuf; Soylu, Mustafa Serkan (ROYAL SOC CHEMISTRY, 2014)
A tetradentate N- and O-donor, N,N-bis(2-hydroxyethyl)-ethylenediamine, (N-bishydeten), has been employed to synthesize four new heterometallic cyanido complexes, [Ni-2(N-bishydeten)(2)Co(CN)(6)]center dot 3H(2)O (C1), [Cu-2(N-bishydeten)(2)Co(CN)(6)]center dot 3H(2)O (C2), [Zn-2(N-bishydeten)(2)Co(CN)(6)]center dot 5H(2)O (C3) and K[Cd(N-bishydeten)-Co(CN)(6)]center dot 1.5H(2)O (C4). Characterization of the complexes was performed using IR and EPR spectroscopy (for C2), thermal analysis and elemental analysis techniques. The crystal structure of C2 was determined by the X-ray single crystal diffraction technique. The asymmetric unit of C2 consists of cyanido-bridged trinuclear Cu1Cu2Co3 units {-CN-Cu1(N-bishydeten)-mu-O-Cu2(N-bishydeten)-NC-Co3(CN)(4)-CN-} and three water molecules. The water molecules are situated in the inter-fragment spaces. The [Cu-2(N-bishydeten)(2)](2+) cations are linked to the [Co(CN)(6)](3-) anions via two cyanido bridges to give a 1D neutral zigzag chain. One of two N-bishydeten cations bridges five coordinated Cu1 and six coordinated Cu2 through deprotonated eta(1)-O2 and the charge of C2 is counterbalanced by this eta(1)-O2. The IR spectrum of C2 is quite different from other complexes, three nu(C N) absorption bands were observed due to different cyanido groups in its structure. The thermal decomposition of C1-C4 is processed in multistages. Variable temperature magnetic susceptibility measurement recorded in the 10-300 K range showed the presence of a strong antiferromagnetic exchange interaction in C2 between Cu1 and Cu2 by eta(1)-O2.
Keywords: ELECTRON-SPIN-RESONANCE; MAGNETIC-PROPERTIES; COPPER(II) COMPLEXES; SUPRAMOLECULAR ARCHITECTURES; BRIDGED HETEROPOLYNUCLEAR; HEXACYANOMETALLATE ANIONS; THERMAL ANALYSES; FE-III; CR-III; TRINUCLEAR; Chemistry